Yolk Binding Treatment for Reticulated Python in House of Pet Clinic: Penanganan Kasus Yolk Binding Pada Ular Sanca batik (Python reticulatus) di Klinik House of Pet - Isnaeni, Intan Kirana; Setianingrum, Ani; Hardian, Andreas Bandang; Yesica, Reza; Herlambang, Anugrah Niki (Faculty of Veterinary Medicine Universitas Brawijaya, 2022)
Yolk binding is a condition where the egg yolk as food reserves while the snake still in the egg phase is notcompletely absorbed in the snake’s body when the snake has become neonatal. This study aims todetermine the handling of cases of yolk binding in Python reticulatus. A 3-month-old female Pythonreticulatus was brought by the owner to the vet with complaints of not defecating after ten days from thelast feeding on and the presence of a ¼ lump from the caudal. The results of the stool examinationshowed the number of protozoa. The x-ray results, show the air-filled medial with radiolucent colorintensity and a mass with radioopaque color intensity. Based on the signals, history, physical examination,and investigations, a diagnosis of yolk binding was obtained. The treatment given is surgery, drug therapy,and post-operative care. After being brought home, five days after surgery snake died.